1998
DOI: 10.2176/nmc.38.131
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after External Decompression for Massive Cerebral Infarction

Abstract: Acute ischemic stroke involving the entire vascular distribution of a carotid or middle cerebral artery can cause massive cerebral edema. This study evaluated external decompression for the treatment of massive stroke and analyzed possible prognostic factors. Twenty-four patients with acute massive cerebral infarction, which had progressed to tentorial herniation and impending death, underwent ex ternal decompression after medical therapy failed to achieve an effective response. The neurological outcome 2 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 18 publications
0
32
0
2
Order By: Relevance
“…465,466 Decompressive surgery, including hemicraniectomy and durotomy with temporal lobe resection, remains the most attractive option for ischemic brain swelling. [692][693][694][695][696][697][698][699][700][701] Timing of surgery is poorly defined, with some opting for early (within 24 hours) intervention. 702 Recent studies have found that decompressive craniectomy may have a less favorable outcome than suggested.…”
Section: A Ischemic Brain Swellingmentioning
confidence: 99%
“…465,466 Decompressive surgery, including hemicraniectomy and durotomy with temporal lobe resection, remains the most attractive option for ischemic brain swelling. [692][693][694][695][696][697][698][699][700][701] Timing of surgery is poorly defined, with some opting for early (within 24 hours) intervention. 702 Recent studies have found that decompressive craniectomy may have a less favorable outcome than suggested.…”
Section: A Ischemic Brain Swellingmentioning
confidence: 99%
“…4 Since that time, several case series or case reports have reported improved survival of patients after craniectomy, but no definitive conclusion has been reached as to any benefit in functional outcomes. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The largest case series 5 suggested that early decompression (ie, Ͻ24 hours) reduces mortality and may provide improved outcomes by avoiding the consequences of brainstem compression from transtentorial herniation. Patients who underwent early hemicraniectomy had a mortality rate of 16% compared with 34% for delayed surgery.…”
mentioning
confidence: 99%
“…Various other scales have been developed, some of which are seldom used outside their country of origin 14 . Examples of these are the Innsbruck coma scale 6 and the Japanese scale 15 . They all generally involve assessing the patient and awarding a score that gives an overall idea of their level of consciousness.…”
Section: Discussionmentioning
confidence: 99%